Bernstein operators of second kind and blending systems - Inoan, Daniela Ioana; Nasaireh, Fadel; Rasa, Ioan (J. Numer. Anal. Approx. Theory, 2017)
We consider the fundamental polynomials associated with the Bernstein operators of second kind. They form a blending system for which we study some shape preserving properties. Modified operators are introduced; they have better interpolation properties. The corresponding blending system is also studied.